The Law of Bribery in the Judiciary: A Comparative Analysis of the Opinions of Yusuf Qardhawi and Asy-Syaukani - Marpaung, Aripin (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
This research focuses on the principle of justice in Islamic law, which is seen as the main foundation for the entire sharia legal system, especially in the context of bribery cases in upholding rights and eliminating injustice. The main objective of this research is to understand the limitations and exceptions related to the law of bribery according to the views of two major scholars, Yusuf al-Qaradawi and Asy-Syaukani, and how the concept of maqasid sharia (the purpose of sharia) is applied in emergency situations that allow the permissibility of bribery. The research method used is a comparative analysis between the two views, by exploring the background of the arguments and the underlying context of Islamic law. The results show that Yusuf al-Qaradawi permits bribery in urgent emergencies, especially when it is the only way to defend a neglected right or eliminate injustice, after all legitimate efforts allowed by religion have been taken. In contrast, Asy-Syaukani forbids bribery absolutely without exception, based on the generality of the hadith that forbids the practice of bribery. In this comparison, Asy-Syaukani's view is considered stronger in terms of evidence, but in the current context, Yusuf al-Qaradawi's view is considered more relevant to the conditions in Indonesia, where bribery is sometimes used as a way to defend rights in urgent situations.The conclusion of this study confirms that the maqasid principle of sharia, which includes the fulfillment of emergency needs (dharuriyyat), general needs (hajiyyat), and refinement (tahsiniyyat), can be the basis for the permissibility of bribery under certain conditions. The legal consequences of bribery in order to defend rights are imposed on the recipient of the bribe and its intermediaries, while the bribe giver is not subject to sanctions because the aim is to claim legitimate rights.